Evaluation of the performance of pharmacists in terms of providing health assistance at a university hospital - Penaforte, Thais Rodrigues; Forster, Aldaisa Cassanho; Simoes, Maria Jacira Silva [UNESP] (Universidade de São Paulo (USP), Hospital das Clínicas, 2007)
OBJETIVE: This study aimed to assess the practices of pharmacists in Hospital Care. Method - we interviewed 20 pharmacists from the Pharmacy Division by applying a structured instrument, in September 2005. This instrument addressed aspects related to the main activities at the Hospital Pharmacy, which were assessed according to indicators organized into five areas: sector management, hospital pharmacotechniques, committee activities, information and pharmacotherapeutic follow-up, as well as teaching and research activities.RESULTS: the Pharmacy Division considered all structural aspects under analysis as essential for the good development and application of its services. We found that some essential services, such as the Medication Information Service and Pharmacotherapeutic Follow-up, were absent. Pharmacist professionals were dissatisfied about human resource and physical structure dimensioning, and they presented as not very active in terms of Pharmaceutical Care.CONCLUSION: Results indicate that care is still centered on the drug, with few clinical activities. We suggest reformulations in service management, particularly in the management of pharmacists.
Keywords: hospital pharmacy service; process and result assessment (Health care); hospital human resources administration; health care quality; hospital pharmacist